2018
DOI: 10.1080/20009666.2018.1444905
|View full text |Cite
|
Sign up to set email alerts
|

Adult idiopathic hypertrophic pyloric stenosis - a common presentation with an uncommon diagnosis

Abstract: Background and Objectives: Adult Idiopathic hypertrophic pyloric stenosis (AIHPS) is a rare but well-defined entity in adults with only 200-300 cases reported so far in the literature.We describe a case of AIHPS and the relevant literature review.Methods and Results: The patient presented with acute onset upper abdominal pain associated with nausea, vomiting, foul-smelling black tarry stools, and anorexia. On the Esophagogastroduodenoscopy (EGD), pylorus demonstrated a unique “cervix sign.” The patient had mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The retained gastric content drained from the nasogastric tube may be caused by the accumulation of undigested food and blood that leaked from the pylorus, which created a foul-smelling and dark-colored material. Hassan, et al [ 8 ] reported similar findings from patient with GOO due to adult idiopathic hypertrophic pyloric stenosis. In GOO, a large amount of food debris is retained because only gastric juice promotes digestion in contrast with small-bowel obstruction, in which food is exposed to pancreatic enzymes that play an important role in digesting food debris [ 9 ].…”
Section: Discussionmentioning
confidence: 60%
“…The retained gastric content drained from the nasogastric tube may be caused by the accumulation of undigested food and blood that leaked from the pylorus, which created a foul-smelling and dark-colored material. Hassan, et al [ 8 ] reported similar findings from patient with GOO due to adult idiopathic hypertrophic pyloric stenosis. In GOO, a large amount of food debris is retained because only gastric juice promotes digestion in contrast with small-bowel obstruction, in which food is exposed to pancreatic enzymes that play an important role in digesting food debris [ 9 ].…”
Section: Discussionmentioning
confidence: 60%
“…9,10 Zarineh et al divided AHPS into primary, which has no underlying cause and under which idiopathic AHPS would be classified, and secondary, caused by an underlying disorder such as excessive healing of gastric or duodenal ulcers, malignant tumors, GISTs, postoperative intraabdominal adhesions, bezoars, and increased vagal activity, causing hypertrophy of the pylorus. 2 The secondary type of AHPS usually demonstrates predominantly localized replacement by fibrous tissue, with little or no smooth muscle hypertrophy. 5 Secondary AHPS often does not present any symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are various classifications, however the most common type of AHPS is secondary to underlying gastrointestinal pathologies, such as peptic ulcer, malignant tumors, and certain inflammatory diseases. 2 Chronic peptic ulcer resulting in gastric outlet obstruction is the least common complication, occurring in approximately 2 percent of cases. 3 Patients with secondary AHPS often do not present any symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…CT imaging may also help to identify secondary causes such as hernia, inflammatory changes, or malignancy. A more reliable sign [16][17][18] to suggest hypertrophic pyloric stenosis is the "cervix sign," which is seen on endoscopy and refers to a fixed smooth narrowing of the pylorus that persists even after anticholinergic administration (►Fig. 10).…”
Section: Adult Hypertrophic Pyloric Stenosismentioning
confidence: 99%
“…It has been classified into three types by Danikas et al as follows: Type 1: infantile adult hypertrophic pyloric stenosis (HPS) diagnosed at a late stage wherein history of symptoms in infancy is present, Type 2: most common type which occurs secondary to other underlying gastrointestinal pathologies, such as hiatus hernia, malignancy, and certain inflammatory diseases, and Type 3: primary idiopathic variety. 16 A more widely accepted classification is into primary and secondary types as reported by Zarineh et al 17 When no underlying pathology can be found, it is classified as primary/idiopathic, and in the presence of an underlying disease such as malignancy, postoperative adhesions, fibrosis consequent to healing of ulcers, etc., it is called as secondary HPS. Patients may present with epigastric pain and distension, which is relieved by vomiting.…”
Section: Miscellaneous Adult Hypertrophic Pyloric Stenosismentioning
confidence: 99%